Penerapan Pengembangan Refugia Dan Parasitoid Trichogramma Sp. Untuk Optimalisasi Konservasi Musuh Alami Pertanaman Cabai Merah Besar Di Desa Andongsari Kabupaten Jember - Muhlison, Wildan; Purnomo, Hari; Sucipto, Irwanto; Haryadi, Nanang Tri (Universitas Mataram, 2024)
Andongsari Village Ambulu District is located in the southern part of Jember, Andongsari village itself is a target village for UNEJ LP2M KKN which is under development into a Prosperous Tourism and Entrepreneurial Village. The majority of people in Andongsari Village work as farmers and agricultural laborers and for general commodities there are rice, corn, cabbage, cauliflower, tobacco and for the main commodity is large chili. Based on the observations of our team, farmers there have been well coordinated through active farmer groups, not only male farmer groups there are also female farmer groups that are also equally active. In addition, farmers there have also known an integrated pest management system by combining chemical, mechanical and biological control systems along with implementing a natural enemy conservation system by planting refugia plants, this is shown by the development of many refugia in each cultivated land. Further search results, the attack of plant disturbing organisms, especially pests in large chili plantations is very high even though the application of synthetic pesticides is high. Excessive application of synthetic pesticides is suspected to be one of the main factors of pest resistance and at the same time the malfunction of refugia technology that has been applied in the field. On the other hand, the application of synthetic pesticides becomes one of the main and largest expenses of large chili production costs. Therefore, to be able to solve these problems, the solutions offered are the first to provide insight into how to identify pests in large peppers and their forms of prevention, the second optimization and arrangement of refugia plant design in cultivated land, the third training and assistance in propagation and conservation of natural enemies (useful insects) as a form of correlation with the refugia system and the last to support the integrated pest management system that has been There is training and assistance in making insecticides and vegetable functions by utilizing vegetable sources from the environment in Andongsari village. So that the farmer group in Andongsari village is able to independently produce refugia, mass multiply natural enemies and produce organic pesticides sustainably and can become an economic business unit for these farmer groups.